MUHAMMAD RASYID RIDHA ANTARA MODERNISME DAN TRADISIONALISME - Harahap, Sumper Mulia (FITRAH:Jurnal Kajian Ilmu-ilmu Keislaman, 2014)
AbstractModernism in Western society presupposes mind, flow, movement and efforts to revamp understanding, customs, and so long institutions to suit the new environment brought by advances in science and modern technology. This idea emerges in the Western with the aim of adjusting the teachings found in Catholicism and Protestantism with modern science. The flow of ideas and eventually lead to the emergence of secularism in Western societies. Islamic modernists are as people who commit a conscious effort to formulate the values and principles of Islam (Islamic values) in accordance with modern thinking or integrate the ideas and institutions into modern Islam. It is regarded as an attempt to make Islam flexible and people can play a role in the current flowing modernity tightly. This effort is to create latitude for Muslims and can get out of a claim, stagnant, not grounded and conservative.Meanwhile, Islamic traditionalism, sometimes called traditional Islam, is covering a broad sense. Traditional Islam is believed to be authentic. It contains the sanctity of tradition, eternity, truth is certain; perennial wisdom, and also the application of sustainable principles of eternal on diverse conditions of space and time. A traditionalist can be defined as a person who has committed the sharia is the source of all religious teachings and morality. Rashid Rida (1865-1935) is known as a traditionalist thinkers because of his ideas and his desire to establish a caliphate institutions. It lived during the Islamic world is facing the rise of Western imperialism and colonialism while traditional Islamic political order is disintegrating. After the defeat of the Ottoman dynasty in World War I and the advent of Kemalism in Turkey, the Turkish Grand National Assembly decided in 1924 to dissolve the caliphate. These events led to a crisis of identity and give political meaning for Muslims, and encourage the rise of Islamic movements such as the movement Salafiah and the Caliphate. Keywords: Muhammad Rashid Rida, Modernism, Traditionalism AbstrakModernisme dalam masyarakat Barat mengasumsikan pikiran, aliran, gerakan dan usaha untuk merubah pemahaman, kebiasaan, dan lembaga begitu lama untuk menyesuaikan dengan lingkungan baru yang dibawa oleh kemajuan ilmu pengetahuan dan teknologi modern. Ide ini muncul di Barat dengan tujuan menyesuaikan ajaran ditemukan di Katolik dan Protestan dengan ilmu pengetahuan modern. Aliran ide dan akhirnya menyebabkan munculnya sekularisme dalam masyarakat Barat.Modernis Islam adalah sebagai orang yang melakukan upaya sadar untuk merumuskan nilai-nilai dan prinsip-prinsip Islam (nilai-nilai Islam) sesuai dengan pemikiran modern atau mengintegrasikan ide-ide dan institusi dalam Islam modern. Hal ini dianggap sebagai upaya untuk membuat Islam fleksibel dan orang dapat berperan dalam arus yang mengalir modernitas erat. Upaya ini adalah untuk menciptakan lintang bagi umat Islam dan bisa keluar dari klaim, stagnan, tidak beralasan dan konservatif.Sementara itu, tradisionalisme Islam, kadang-kadang disebut Islam tradisional, meliputi arti luas. Islam tradisional diyakini otentik. Ini berisi kesucian tradisi, keabadian, kebenaran yang pasti; kebijaksanaan abadi, dan juga penerapan prinsip-prinsip berkelanjutan abadi pada kondisi yang beragam ruang dan waktu. Sebuah tradisionalis dapat didefinisikan sebagai orang yang telah melakukan syariah adalah sumber dari semua ajaran agama dan moralitas.Rasyid Ridha (1865-1935) dikenal sebagai pemikir tradisionalis karena ide-idenya dan keinginannya untuk mendirikan sebuah lembaga kekhalifahan. Ini hidup pada dunia Islam menghadapi munculnya imperialisme Barat dan kolonialisme sementara pesanan politik Islam tradisional hancur. Setelah kekalahan dari dinasti Ottoman dalam Perang Dunia I dan munculnya Kemalisme di Turki, Turki Grand Majelis Nasional memutuskan pada tahun 1924 untuk membubarkan kekhalifahan. Peristiwa ini menyebabkan krisis identitas dan memberikan makna politik bagi umat Islam, dan mendorong munculnya gerakan-gerakan Islam seperti gerakan Salafi dan Khilafah. Kata Kunci : Muhammad Rasyid Ridha, Moderenisme, Tradisonalisme